Audits Quality in Mediating Profitability, Liquidity, Audit Lag, Prior Opinion on Accepting Going Concern Audits - Mulyawati, Anugrana; Munandar, Agus (Interdisciplinary Social Studies, 2022)
Researchers believe that research on audit opinion going concern will continue to be interesting as a research material on an ongoing basis, this is because the going concern audit opinion  can be an important signal for companies in determining management policies and also become a consideration for investors in investing their money. This research aims to analyze the role of audit quality in mediating the influence of profitability, liquidity, audit lag, and prior opinion on the acceptance of audit opinion going concerned. Purposive sampling technique is used for sample processing, and companies that fit the sampling criteria are as many as 17 companies in the year of the research period (2015-2019), then the total observations processed are 85 samples. The research methodology uses the SPSS program with hypothesis testing using logistic regression analysis. From the results of the test, the prior opinion variable can partially affect the quality audit, and the variables of profitability, liquidity, and audit lag do not affect the quality of the audit. Then, the results of partial tests of audit opinions going concerned with profitability and prior opinion are influential, but liquidity and audit lag does not have an effect. The results of audit quality variable tests on audit opinions have a significant influence. The results of the track analysis prove that audit quality variables cannot mediate variables of profitability, liquidity, audit lag, and prior opinion to audit opinion going concerned.